2021
DOI: 10.3390/biomedicines9111608
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the TIGIT, CD226, CD112, and CD155 Immune Checkpoint Molecules in Peripheral Blood Mononuclear Cells in Women Diagnosed with Early-Onset Preeclampsia

Abstract: Early-onset preeclampsia is a common obstetrical disease with a potential genetic background and is characterized by the predominance of Th1 immune response. However, although many studies investigated the immunological environment in preeclamptic patients, no information is available about the potential role of the TIGIT/CD226/CD112/CD155 immune checkpoint pathway. A total of 37 pregnant women diagnosed with early-onset preeclampsia and 36 control women with appropriately matched gestational age were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In another study, it was found that the proportion of Tight + CD8 + T to CD8 + in the peripheral blood of NP women was approximately 20%‐30% 98 . Expression of CD226, CD112, and CD155 was detected in T cells, NK cells, and monocyte subsets in PBMC of the NP group 99 …”
Section: Next Generation Of Inhibitory Immune Checkpoint Moleculesmentioning
confidence: 93%
See 3 more Smart Citations
“…In another study, it was found that the proportion of Tight + CD8 + T to CD8 + in the peripheral blood of NP women was approximately 20%‐30% 98 . Expression of CD226, CD112, and CD155 was detected in T cells, NK cells, and monocyte subsets in PBMC of the NP group 99 …”
Section: Next Generation Of Inhibitory Immune Checkpoint Moleculesmentioning
confidence: 93%
“…99,101 Decreased CD226 expression and increased CD112 and CD155 surface expression were found in all T cell, NK cell, and monocyte subpopulations in women diagnosed with PE compared to the healthy group. 99 Blocking Tigit (PxxP, two in CD28 and one in CTLA-4). 103 Although it lacks classic ITIM or ITSM motifs in the cytoplasmic domain, the protein sequence contains potential protein kinase C binding sites and a proline-rich motif, which may function as a platform for interaction with other complexes (Table 1).…”
Section: Tigit Signaling In Normal Pregnancy and Pregnancy Complicationsmentioning
confidence: 93%
See 2 more Smart Citations
“…We did not detect any significant difference between the sCD226 levels or during the regression analyses between the surface or the relative expression of CD226. It is possible that the CD226 molecule shed from the surface of NKT cells does not stay too long in circulation but interacts with the increased amount of CD112 and CD155 ligands expressed by the monocytes, NK and T cell subsets [ 52 ]. This interaction can block these ligands from connecting with surface TIGIT or CD226 receptors.…”
Section: Discussionmentioning
confidence: 99%